Compliment piropo in Spanish space - Elena V. Astakhova (Ибероамериканские тетради, 2016)
The article analyzes the Spanish compliment piropo as a special form of language communication which is directly connected to popular culture, covers diﬀerent aspects of life and is related with studies of national character, saving or abandoning traditions and old values. The compliment piropo reﬂects particular features of historical, literal, social and physiological events experienced by Spanish society. The phenomenon of piropo shows global transformations in the economy, policy, social and gender relationship of Spanish society during the last third of the twentieth and early twenty-ﬁrst century.